Inovações tecnológicas na produção da farinha de tapioca em Abaetetuba-PA - GOMES, Graciete Pereira (2019)
Tapioca flour is a characteristic product of the State of Pará, produced from manioc starch (Manihot esculenta Crantz), which can be found in supermarkets and commerce in the national territory. It is a product that has undergone many transformations in the productive processes, to meet a growing demand. The objective of this work is to analyze the factors that influenced the social and technological changes related to the production of tapioca flour. The research was carried out in the community of Santa Teresinha do Menino Jesus, km 14 of the Rural Area of Abaetetuba-Pará, in the months of March and May of 2019 with family farmers who produce the tapioca meal, through interviews with 7 families. As main results, there were changes in the artifacts, including mechanization, with a consequent increase in the production of tapioca flour, besides the decrease in working time. From the considerable changes, the farmers presented an essential growth in the production of tapioca flour, being able to produce more in less time, stimulating also to extend their areas of cassava cultivation for the future increase of the production of the starch, main product for the manufacture of tapioca flour.